Determinan Fraudulent Financial Reporting di Indonesia dan Malaysia - Muhammad Aufa; Nabila nabila (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
This study was conducted to prove the effectiveness of the fraud pentagon theory on fraudulent financial reporting as proxied by variables of financial stability, quality of external auditor, change in auditor, change in director, and the frequent number of CEO's pictures. The population used in this study were all manufacturing companies registered in Indonesia and Malaysia in 2019-2020 with the purposive sampling technique. There are 166 manufacturing companies in Indonesia and 184 companies in Malaysia that pass the research criteria. The results showed that the variables of financial stability, change in auditor, change in director, and the frequent number of CEO's pictures did not affect fraudulent financial reporting, but the quality of external auditor variable affected fraudulent financial reporting in manufacturing companies in Indonesia. While in Malaysia the variables of quality of external auditor, change in auditor, change in directors and the frequent number of CEO's pictures have no effect on fraudulent financial reporting, but financial stability variables affect fraudulent financial reporting in manufacturing companies in Malaysia.